2016
DOI: 10.1016/j.foodhyd.2016.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal films based on starch-gelatin blend, containing essential oils

Abstract: The antimicrobial activity of essential oils (EO) is very well-known and it has been 13 reported that incorporating them into edible films based on biopolymers extends the 14 food's shelf-life. In this study, cinnamon, clove and oregano EO, at 25% with respect to 15 the polymer, were incorporated into glycerol plasticized starch-gelatin blend films (ratio

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(70 citation statements)
references
References 33 publications
2
60
2
2
Order By: Relevance
“…Studies of films with gelatin and incorporation of 5% bergamot essential oil and 15% lemongrass essential oil resulted in WVP values of 12.6 × 10 −11 and 10 × 10 −11 g Pa −1 s −1 m −1 , respectively . These results are surprisingly positive, once the main component of TTO, terpinen‐4‐ol, is less hydrophobic than limonene, the main component of citric oils like bergamot . Studies with 2% of TTO in chitosan matrix and hydroxypropyl‐methylcellulosebased films reported WVP values of 74.7x10 −11 and 57.3 × 10 −11 g Pa −1 s −1 m −1 , respectively .…”
Section: Resultsmentioning
confidence: 99%
“…Studies of films with gelatin and incorporation of 5% bergamot essential oil and 15% lemongrass essential oil resulted in WVP values of 12.6 × 10 −11 and 10 × 10 −11 g Pa −1 s −1 m −1 , respectively . These results are surprisingly positive, once the main component of TTO, terpinen‐4‐ol, is less hydrophobic than limonene, the main component of citric oils like bergamot . Studies with 2% of TTO in chitosan matrix and hydroxypropyl‐methylcellulosebased films reported WVP values of 74.7x10 −11 and 57.3 × 10 −11 g Pa −1 s −1 m −1 , respectively .…”
Section: Resultsmentioning
confidence: 99%
“…However, the drawbacks of starch‐based films include poor mechanical properties. To overcome this drawback, starch has been blended with chitosan, gelatin, and whey protein to form composites, and antimicrobial and antioxidant agents have been incorporated …”
Section: Introductionmentioning
confidence: 99%
“…Além disso, o aumento da elongação de determinados filmes e a melhora da sua tenacidade são características interessantes dentro da área de embalagens. 6,[28][29][30][31][32][33] Na Figura 3-A observa-se que o filme controle (FG) possui uma superfície compacta, lisa e homogênea sem estrutura granulada e porosa, sem a presença de separações de fase, sugerindo que uma matriz mais ordenada foi formada. Nos filmes elaborados com a nanoemulsão de óleo essencial de limão (Figura 3-B) também não foi observada a separação da fase oleosa.…”
Section: Resultsunclassified